PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI (Studi Empirik Pegawai Pada Pesantren Ibnu Taimiyah Bogor) - Suhendi, Suhendi; Entang, Mohammad; Tukiran, Martinus (Universitas Pakuan, 2023)
The purpose of this study is to determine the influence of Organizational Culture and Transformational Leadership on organizational commitment through the mediation of work motivation. The study population was 144 employees at the Ibnu Taimiyah Islamic Boarding School in Bogor and a sample of 106 employees. Data collection for each variable studied used a questionnaire with an assessment scale. Data analysis techniques using descriptive statistical analysis techniques and path analysis techniques (path analysis). The results showed: (a) There is a direct influence between organizational culture on work motivation with a regression coefficient value of β = 0.875, (b) There is a direct influence between transformational leadership on work motivation with a regression coefficient value of β = 0.035, (c). There is a direct influence between organizational culture on organizational commitment with a regression coefficient value of β = 0.421, (d). There is a direct influence between transformational leadership on organizational commitment and the value of the regression coefficient of β = 0.268, (e). There is a direct influence between work motivation and organizational commitment and the value of the regression coefficient of β = 0.303, (f). There is an indirect influence between organizational culture on organizational commitment through work motivation with a zhitung value greater than ztabel or 2,171 1.96. Then it can be concluded that work motivation mediates the indirect influence between organizational culture on organizational commitment, and (g). There is an indirect influence between transformational leadership on organizational commitment through work motivation with a zhitung value smaller than ztabel or 0,565 1.96. So it can be concluded that work motivation mediates the indirect influence between transformational leadership and organizational commitment.